The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1186/s12891-021-04855-9
|View full text |Cite
|
Sign up to set email alerts
|

Calcaneal lengthening using ipsilateral fibula autograft in the treatment of symptomatic pes valgus in adolescents

Abstract: Background Evans calcaneal lengthening osteotomy is used to treat symptomatic flexible flatfoot when conservative treatment fails. Grafts such as autologous iliac bone grafts, allografts, and xenografts are implanted at the osteotomy site to lengthen the lateral column of the hindfoot. This study aimed to present the outcomes of an autologous mid-fibula bone graft used for calcaneal lengthening in symptomatic pes valgus in adolescents. Methods We r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
1
1
1
Order By: Relevance
“…We also found improvement in pain and mobility PROMIS scores among patients undergoing this procedure. Our findings are similar to those of previous studies which reported improvement in American College of Foot and Ankle Surgeons (ACFAS) and American Orthopedic Foot & Ankle Society (AOFAS) scores after CLO 9,13,19–23 . Importantly, we found no statistical differences in pain and mobility PROMIS scores between the K-wire and the plate fixation group at follow-up.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We also found improvement in pain and mobility PROMIS scores among patients undergoing this procedure. Our findings are similar to those of previous studies which reported improvement in American College of Foot and Ankle Surgeons (ACFAS) and American Orthopedic Foot & Ankle Society (AOFAS) scores after CLO 9,13,19–23 . Importantly, we found no statistical differences in pain and mobility PROMIS scores between the K-wire and the plate fixation group at follow-up.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are similar to those of previous studies which reported improvement in American College of Foot and Ankle Surgeons (ACFAS) and American Orthopedic Foot & Ankle Society (AOFAS) scores after CLO. 9,13,[19][20][21][22][23] Importantly, we found no statistical differences in pain and mobility PROMIS scores between the K-wire and the plate fixation group at follow-up. In both cohorts, compared with preoperative scores, mobility scores achieved a clinically notable improvement at 12 months, but pain scores improved as early as 6 months.…”
Section: Discussioncontrasting
confidence: 57%
“…When analysing radiographs of the foot in children aged 6 to 12 years, some authors found that the values of the main 11 clinical useful angles change with age. To evaluate the main radiological parameters, it is necessary to take into account the age of patients, as well as anthropometric data [23,26,33]. The analysis of the radiological parameters of the foot in children aged 12-17 years shows that the range of differences in the indicators is within 20⁰-25⁰.…”
Section: оригінальні дослідження ортопедіяmentioning
confidence: 99%